2016
DOI: 10.3389/fpsyg.2016.01908
|View full text |Cite
|
Sign up to set email alerts
|

Typing Style and the Use of Different Sources of Information during Typing: An Investigation Using Self-Reports

Abstract: We investigated to what extent different sources of information are used in typing on a computer keyboard. Using self-reports 10 finger typists and idiosyncratic typists estimated how much attention they pay to different sources of information during copy typing and free typing and how much they use them for error detection. 10 finger typists reported less attention to the keyboard and the fingers and more attention to the template and the screen than idiosyncratic typists. The groups did not differ in attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(79 reference statements)
2
11
1
Order By: Relevance
“…Hunt-and-peck typists often have to look at the keyboard to find the exact position of the required key. Correspondingly, ten-finger typists report that they use kinesthesis/touch and internal monitoring more often in order to detect an error than idiosyncratic typists [34]. Therefore, we expected to find that error detection in ten-finger typists relies relatively more on kinesthetic/tactile feedback and the screen, whereas error detection in hunt-and-peck typists relies relatively more on visual feedback from the keyboard and fingers [34].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hunt-and-peck typists often have to look at the keyboard to find the exact position of the required key. Correspondingly, ten-finger typists report that they use kinesthesis/touch and internal monitoring more often in order to detect an error than idiosyncratic typists [34]. Therefore, we expected to find that error detection in ten-finger typists relies relatively more on kinesthetic/tactile feedback and the screen, whereas error detection in hunt-and-peck typists relies relatively more on visual feedback from the keyboard and fingers [34].…”
Section: Introductionmentioning
confidence: 91%
“…Correspondingly, ten-finger typists report that they use kinesthesis/touch and internal monitoring more often in order to detect an error than idiosyncratic typists [34]. Therefore, we expected to find that error detection in ten-finger typists relies relatively more on kinesthetic/tactile feedback and the screen, whereas error detection in hunt-and-peck typists relies relatively more on visual feedback from the keyboard and fingers [34]. We further expected that ten-finger typists differ less in the use of sources for error detection in MI and ME than hunt-and-peck typists, because ten-finger typists presumably have more precise internal models of typing [14].…”
Section: Introductionmentioning
confidence: 99%
“…Slow typists use less rollover (8% versus 50%). They rely more on visual search [5,32] and use fewer fingers, which restricts the use of rollover.…”
Section: Discussionmentioning
confidence: 99%
“…They argued that trained touch typists are able to type more rapidly because they use more fingers and type more consistently, using the same finger for a given key. Rieger and Bart [32] compared touch typists and 'idiosyncratic' (non-touch) typists and found that faster typists rely less on visual information about the typing process (e.g. location of fingers on keyboard).…”
Section: Typing On Modern Keyboardsmentioning
confidence: 99%
See 1 more Smart Citation